Reducing computational costs in site response analysis and its application for the nonlinear dynamic analysis of structures. (December 2022) - Majidi, Noorollah; Tajmir Riahi, Hossein; Mahdi Zandi, Sayed
Abstract: In this paper, the wavelet transform is used for the first time to reduce the cost of site response analysis calculations for different soil profiles in Isfahan city. This downsampling method was used up to three levels to generate approximate waves from the ground motion records. Site response analysis was done using the one-dimensional equivalent linear and nonlinear method. Down-hole seismic tests of 71 boreholes in Isfahan city were used to make different soil profiles. In addition, 30 ground motions compatible with seismic hazard analysis of this city were selected. Due to the lack of comprehensiveness in previous studies, none of them has definitively indicated which level of wave decomposition is the last reliable wavelet filter. But in this article, for the first time, by performing a data reliability review, it is shown that the last reliable filter for the site response is related to the second level of decomposition. Comparison of the site response analysis using approximate waves and the main records, by performing more than 2100 analyses, showed that wavelet transform could be used up to two levels with the maximum error of 8% in predicting amplification factors. In addition, approximate waves were used for the nonlinear dynamic analysis of structures with different heights located at different soil profiles, and results showed that wavelet transform decreases the cost of calculations up to 50% with a 5% error.